EXAMPLES OF LESSON PLANS FOR TEACHING ENGLISH IN HIGH SCHOOL - da Silva, Rosiane Pereira (Seven Editora, 2026)
This chapter presents examples of lesson plans for teaching English in high school, focusing on the development of reading, text interpretation, vocabulary expansion, and cultural understanding. The pedagogical proposals use texts with narratives, scientific curiosities, historical facts, literature, cinema, and contemporary themes to stimulate meaningful and critical learning among students. The lesson plans address different methodological strategies, such as pre-text activities, skimming, scanning, debates, dramatizations, interviews, guided reading, and interpretation exercises. These activities encourage the development of linguistic skills and student autonomy in the English language learning process. The content explored includes varied themes such as popular legends ("Jack o’ Lantern"), scientific and technological advances, genetics, the environment, health, media, American culture, labor rights, superheroes, natural phenomena, and social issues. The contextualization of the content seeks to bring teaching closer to the students’ reality, promoting critical reflection, social interaction, and knowledge construction. Beyond textual comprehension, the lesson plans emphasize the study of vocabulary, verb tenses, phrasal verbs, grammatical structures, and discursive aspects of the English language. Assessments are continuous, considering participation, interpretation, oral production, debates, problem-solving exercises, and group activities. This chapter highlights the importance of pedagogical planning combined with dynamic and contextualized methodologies, demonstrating that English language teaching in high school can contribute to the linguistic, cultural, critical, and social development of students.